Web-based English Competency Assessment and Placement System For Faculty Communication and Modern Languages. - Salem, Amer Salem Ali (2007)
English is a dominant world language with second largest speaking population after mother tongue. Choosing study English as a second language is a wise choice at these globally competitive times. English brings people from various nationalities towards international communication. It's key to speak to the world. The goal of this research project is to "design a web-based English competency evaluation and regulation for Faculty of Communication and Modern Languages (or FKBM, its Malay short form)"- that can support new students to overcome their English language proficiency and help to FKBM to estimate students level of English competency and allocate relevant course for registration.